Pengaruh Audit Fee, Rotasi Auditor dan Ukuran Perusahaan Terhadap Kualitas Audit Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Terdaftar di Bursa Efek Indonesia 2018-2020. - Lutfil Khakim; Lestari, Utami Puji (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The objectives of this research: 1) To find out and analyze the influence of Audit Fees on quality; 2) knowing and analyzing auditor rotation on audit quality; 3) knowing and analyzing company size on audit quality. The population in this research is all company data in the Consumer Goods industry sector listed on the Indonesia Stock Exchange (BEI) from 2018 to 2020, totaling 52 companies. This research used a sampling method with a purposive sampling technique to obtain a sample of 27 companies or 81 data samples. The analysis technique used is logistic regression. The results of this research can be concluded that the Audit Fee variable has no effect on audit quality, and auditor rotation has no effect on audit quality. Meanwhile, company size influences audit quality.